Factors influencing mosaicism: a retrospective analysis. Issue 3 (September 2022) - Huang, Qiu-Xiang; Wang, Zhi-Hong; Huang, Wu-Jian; Mao, Li-Hua; Lin, Chun-Li; Chen, Guo-Yong; Wang, Cai-Xia; Chen, Zhi-Biao; Lin, Yu-Lin; He, Ling-Yun; Liu, Yun
Abstract: Research question: What factors affect the incidence of mosaic embryos resulting from assisted reproductive technology? Design: A retrospective analysis of data from preimplantation genetic testing for aneuploidies in 544 couples was conducted using data from an electronic medical record database. Results: Of 1910 embryos studied, 127 (6.6%) were mosaic. In multivariable logistic regression analysis, mosaicism incidence increased in embryos from IVF versus intracytoplasmic sperm injection (ICSI) (odds ratio [OR] 4.560, 95% confidence interval [CI] 2.800–7.424, P < 0.001), and in embryos from abnormal versus normal semen (OR 3.496, 95% CI 2.455–4.979, P < 0.001). Embryos tested using SurePlex 24Sure had lower mosaicism percentages than those tested using MALBAC-NGS and PicoPLEX GenetiSure (OR 2.726, 95% CI 1.532–4.852, P  = 0.001; OR 2.389, 95% CI 1.537–3.711, P < 0.001, respectively). Conclusions: Semen quality, fertilization method and detection system are independent factors associated with embryonic mosaicism.